Entrepreneurial Readiness of Students in Entrepreneurship Courses: SEM Analysis of Family Background, Motivation, and Character - Suharto, Suharto; Andrini, Vera Septi; Hidayati, Umi; Etika, Erdyna Dwi; Sandy, Teguh Arie (Journal La Edusci, 2026)
This study examines the factors influencing entrepreneurial readiness among students enrolled in entrepreneurship courses at Universitas PGRI Mpu Sindok Nganjuk. Specifically, it explores the roles of family background, motivation, character, and entrepreneurship education in shaping students' preparedness to engage in entrepreneurial ventures. Data was collected from 200 students using a structured questionnaire, and Structural Equation Modeling (SEM) was used to analyze the relationships between these factors. The results indicate that family background and entrepreneurship education significantly impact both entrepreneurship course participation and entrepreneurial readiness. Motivation and character, while positively associated with the outcomes, did not show statistically significant effects on entrepreneurial readiness. These findings suggest the importance of early exposure to entrepreneurship and the critical role of formal education in enhancing students' readiness to start their own businesses. The study highlights the need for curricula that integrate both theoretical knowledge and practical, hands-on entrepreneurial experiences.